Strategi Komunikasi Persuasif dalam Menghadapi Stigma Kesehatan Mental Menggunakan Pendekatan Inklusif - Arafah, Rizka Aulia; Destiwati, Rita (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
Optimal individual well-being is often correlated with well-maintained mental health. However, the phenomenon of mental illness has increased significantly in various countries, with the increase in mental illness being dominated by Generation Z. Generation Z lives in a modern era with high environmental pressures that can easily disrupt mental health. The main characteristics of an unfavorable environment towards mental health phenomena and issues are environments that still have a lot of stigma and discrimination against individuals with mental health disorders. This study aims to analyze inclusive persuasive communication strategies in dealing with stigma and strengthening public acceptance of stigma and individuals experiencing mental health problems. This study uses qualitative research using Erving Goffman's Stigmatization Theory, Hovland's Persuasive Communication, and the development of Persuasive Communication Strategies with an Inclusive Approach Melvin L. Defleur and Sandra J. Ball-Rokeach. The results showed that persuasive communication strategies need to involve skills to be responsive in reading and interpreting signals given by individuals with mental health disorders. This is supported by exposure to meaning construction strategies that mental health issues require social attention and support.